PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PROSTITUSI OLEH KEPOLISIAN RESORINDRAGIRI HILIR - Amri, Ruhul; ', Erdianto; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
At this time the level of poverty in Indonesia has increased very high this is due to the deterioration of our country's economy, resulting in the number of companies forced to close his business, it is that trigger the public to be able to find any job that can sustain daily life both legal and illegal, this also trigger the occurrence of social problems in Indonesia one of the most prominent is the emergence of prostitutes or prostitution practices from both young women to middle-aged women. The purpose of this study is to determine the authority of the police to enforce legal action against prostitution crime, police action against pimps and prostitutes, and efforts made to overcome obstacles faced in law enforcement of prostitution crime by Indragiri Hilir Resort Police.The type of this research is sociological legal research whereas if viewed from the nature of this research is descriptive. This research uses primary data that is data obtained directly from the source pertama.dan secondary data that is data that has been so.The result of this research is the authority of the police to enforce the law against the crime of prostitution is done only to the rules set forth in the Criminal Code Article 284, 295, 296. 297, 506 and Law Number 21 Year 2007 on the Crime of Trafficking Persons to cause deterrent effect actors Indragiri Hilir Resort Police action against pimps and prostitution actors in addition to applying the article of the Criminal Code, has also conducted the control of places - places where allegedly providing sexual services and conduct coaching of commercial sex workers caught. The obstacles found by Indragiri Hilir Police in in law enforcement against prostitution crime is the absence of strict regulation to arrange PSK and consumer using PSK services. The existing regulations are only firmly binding for commercial sex service providers ie pimps or pimps. Indragiri Hilir Resort Police can only conduct curbing and only catch commercial sex workers who then only given coaching without being able to catch the CSWs and consumers who receive the services of commercial sex workers. At the time of the arrest operation, much information came to the ears of the prostitutes so that they were prepared to anticipate and escape before the operation was carried out and at the time of raiding the prostitutes and those who were caught by the raid were only recorded, and given directions without any sanction of detention . The efforts undertaken to overcome these obstacles are the Indragiri Hilir Resort Police conducting preventive measures ie preventive business manifested in activities to prevent prostitution and repressive curative activities to suppress (eliminate), and efforts to heal the perpetrators of prostitution to bring they are on the right path.